Increased Risk of Death Triggered by Domestic Violence, Hunger, Suicide, Exhausted Health System during COVID-19 Pandemic: Why, How and Solutions - David, Kenneth Bitrus; Aborode, Abdullahi Tunde; Olaoye, Damilola Quazeem; Enang, Ndikpongkeabasi Victor; Oriyomi, Aboaba Kazeem; Yunusa, Ismaeel (Frontiers in Sociology, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections, just like many other public health emergencies, is a well-established global health burden that has resulted in several changes in routines and lifestyles of people globally. The coronavirus disease (COVID-19) pandemic, caused by SARS-CoV-2, has directly or indirectly involved in the loss of lives of more than 3.24 million as of 6th May, 2021. The increasing threats posed by this pandemic were subsided by the swift and drastic measures put in place by different countries. As other causes of death before the emergence of COVID-19 still exist, the pandemic has further worsened their impact. The increased risks of COVID-19 deaths are not only due to the health burden it possesses, but also due to some other factors. These factors include domestic violence that becomes rampant, especially during lockdowns; hunger due to low economic development, unemployment, and loss of jobs; suicide due to depression; exhausted health system due to high level of COVID-19 cases and inability to contain it. As we move from the response phase into recovery, the pandemic’s direct and broader impacts on individuals, households, and communities will influence the capacity to recover. An understanding of these impacts is therefore required to develop priorities to support recovery. This paper identifies other causes of death amidst the pandemic, such as domestic violence, hunger, suicide, and exhausted health system, and how to minimize their effects.